Sequelae from meningococcal meningitis in children: a critical analysis of dexamethasone therapy Seqüelas de meningite meningocócica em crianças: análise crítica da utilização da dexametasona - Erasmo Barbante Casella; Saul Cypel; André Alexandre Osmo; Yassuhiko Okay; Beatriz Helena Lefèvre; Ida Lichtig; Maria Joaquina Marques-Dias (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To evaluate the effectiveness of dexamethasone as an adjunctive therapy to antibiotics in children with meningococcal meningitis. METHOD: A total of 81 children diagnosed with meningococcal meningitis hospitalized in sequence were studied at the University Hospital of São Paulo University, with the objective of evaluating the presence of sequelae in four different groups of patients, following the administration of dexamethasone: Group I - 25 patients who received the first dose at least 10 minutes before the introduction of the antibiotic therapy; Group II - 19 patients who received the corticosteroid concomitantly; Group III - 14 patients for which the dexamethasone was administered after beginning the antibiotic scheme; Group IV - 23 patients that did not receive dexamethasone. The groups were evaluated for homogeneity through the prognostic indexes and clinical and laboratory characteristics, based on the records obtained at hospitalization. RESULTS: Some degree of sequelae occurred in 16 (26.22%) of the survivors and 23 patients (28.39%) coursed with sequelae or died. The mean period of neurological attendance was 36.97 months and neurological alterations were detected in 16.17% of the patients. No significant difference was found between the four groups. There was also no statistical difference in the comparison of the neurological sequelae in the children from group IV with the children of groups I and II or even with groups I, II and III analyzed as a whole. The presence of hearing loss occurred in 11.11% of the patients, again there was no significant difference between the four groups. Psychological evaluation was performed using the WPSSI and WISC tests. A mild mental disability was detected in one patient from group I and another in group III. The overall analysis of the sequelae (neurological, auditory and intellectual level) also did not demonstrate any significant difference between the four groups. Comparing the children from groups I and II together and also groups I, II and III as a whole with the children in group IV also failed to detect a significant difference arising from the use or nonuse of the corticosteroid. CONCLUSION: Dexamethasone was not proven to be effective in decreasing the number of sequelae among patients with meningococcal meningitis. OBJETIVO: Avaliar a eficácia da dexametasona como uma terapia adjunta à antibioticoterapia em crianças com meningite meningocócica. MÉTODO: Foram avaliadas 81 crianças com diagnóstico de meningite meningocócica e hospitalizadas sequencialmente no Hospital Universitário da Universidade de São Paulo, com o objetivo de avaliar a presença de sequelas em 4 diferentes grupos de pacientes, segundo a administração da dexametasona: Grupo I - 25 pacientes, que receberam a primeira dose pelo menos 10 minutos antes da introdução da antibioticoterapia; Grupo II - 19 pacientes que receberam o corticosteróide de modo concomitante à antibioticoterapia; Grupo III - 14 pacientes, nos quais a dexametasona foi administrada após o início do esquema antibiótico; Grupo IV - 23 pacientes que não receberam dexametasona. A avaliação das características clínicas e laboratoriais no momento da internação demonstrou que os 4 grupos poderiam ser considerados homogêneos. RESULTADOS: Algum grau de sequela ocorreu em 16 (26,22%) dos sobreviventes e 23 pacientes (28,39%) apresentaram sequelas ou faleceram. O período médio de seguimento neurológico foi 36,97 meses e foram detectadas alterações neurológicas em 16,17% dos pacientes. Não se observaram diferenças significativas em relação a presença de seqüelas neurológicas entre os 4 grupos, não havendo também diferenças entre as crianças do grupo IV em relação ao agrupamento das crianças dos grupos I e II ou mesmo I, II e III. A presença de disacusia ocorreu em 11,11% dos pacientes, também não havendo diferenças entre os 4 grupos. A avaliação psicológica foi realizada através dos testes WPSSI and WISC. Foi detectada a presença de deficiência mental leve em um paciente do grupo I e em outro do grupo III. A avaliação global das sequelas (neurológicas, auditivas e cognitivas) também não mostrou haver diferenças significativas entre os 4 grupos. A comparação conjunta das crianças dos grupos I e II e também dos grupos I, II e III com as do grupo IV, também não permitiu a verificação da presença de diferenças significativas em relação a utilização ou não do corticosteróide. CONCLUSÃO: A dexametasona não foi efetiva na redução de sequelas em crianças com meningite meningocóccica.